The Impact of student feedback on educational quality - Mickovska, Bjanka (2025)
This thesis explores how student feedback influences educational quality within master’s programs taught in English at the Faculty of Informatics and Statistics. By combining sentiment analysis of student survey responses with thematic insights from structured interviews, the study evaluates the effectiveness of teaching methods, course design, and feedback systems. Special attention is given to the university’s use of digital platforms, such as INSIS, for feedback collection. Results highlight a strong student preference for courses with clear structure, practical orientation, and responsive instruction. However, concerns emerged regarding the transparency and perceived impact of feedback mechanisms. Statistical analyses (Spearman correlation and chi-square test) and visual data representations reveal limited but insightful links between student sentiment and academic performance. The research concludes that while feedback systems hold potential for institutional improvement, their value depends on better communication, system design, and responsiveness. The findings inform actionable recommendations to enhance student engagement and feedback efficacy.